Analysis of English-Indonesian Translation: Examining Translation Methods in 'The Yellow Wallpaper’ - Etan, Diva Aura Lintang; Sulistyani, Ummi Nur Laila (LITPAM, 2026)
This study investigates the translation methods employed in the Indonesian version of Charlotte Perkins Gilman’s The Yellow Wallpaper based on Newmark’s framework and examines how the dominant method affects the preservation of the narrator’s unreliable first-person voice and deteriorating mental condition. Using a descriptive qualitative design, this study analyzed 389 paired sentences from the source text and the target text. The findings show that target-language-oriented methods dominate the translation, with communicative translation occurring most frequently (195 instances; 50.1%), followed by free translation (78 instances; 20.1%), while source-language-oriented methods are used only marginally. These results suggest that the translator prioritizes readability, naturalness, and acceptability for Indonesian readers over close adherence to the original structure and stylistic form. In particular, communicative translation, often realized through explicitation, helps convey the story’s psychological tension, thematic meaning, and emotional force to the target audience, although some stylistic nuances of the original are reduced. Overall, the study indicates that communicative translation is effective in maintaining the narrative accessibility and literary impact of the work in Indonesian.